Immune-mediated tubule atrophy promotes acute kidney injury to chronic kidney disease transition - Leyuan Xu; Jiankan Guo; Dennis G. Moledina; Lloyd G. Cantley (Nature Communications, 2022)
Acute kidney injury can lead to chronic kidney disease. Here the authors show that the transition is related to a macrophage-mediated second wave of inflammatory cells that promote late tubule injury, dedifferentiation and fibrosis. Suppressing this second wave reduced tubular loss and kidney atrophy.